1996
DOI: 10.1091/mbc.7.10.1639
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast pkl1 is a kinesin-related protein involved in mitotic spindle function.

Abstract: We have used anti-peptide antibodies raised against highly conserved regions of the kinesin motor domain to identify kinesin-related proteins in the fission yeast Schizosaccharomyces pombe. Here we report the identification of a new kinesin-related protein, which we have named pkl1. Sequence homology and domain organization place pkl1 in the Kar3/ncd subfamily of kinesin-related proteins. Bacterially expressed pkl1 fusion proteins display microtubule-stimulated ATPase activity, nucleotide-sensitive binding, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(188 citation statements)
references
References 81 publications
13
174
1
Order By: Relevance
“…pombe has two KAR3 homologs, pkl1 ϩ and klp2 ϩ (Pidoux et al, 1996;Troxell et al, 2001). Neither of these kinesins is essential, either individually or together, but null mutants have altered sensitivities to TBZ and severe meiotic phenotypes.…”
Section: Interactions With Other Kinesinsmentioning
confidence: 99%
See 1 more Smart Citation
“…pombe has two KAR3 homologs, pkl1 ϩ and klp2 ϩ (Pidoux et al, 1996;Troxell et al, 2001). Neither of these kinesins is essential, either individually or together, but null mutants have altered sensitivities to TBZ and severe meiotic phenotypes.…”
Section: Interactions With Other Kinesinsmentioning
confidence: 99%
“…The Schizosaccharomyces pombe genome encodes nine kinesin-related genes from seven subfamilies and one cytoplasmic dynein (Hagan and Yanagida, 1990;Pidoux et al, 1996;Yamamoto et al, 1999;Brazer et al, 2000;Browning et al, 2000;Troxell et al, 2001; pombe genome project). Among the kinesin subfamilies found in fission yeast, three have direct effects on microtubule dynamics and higher order microtubule organization (Goldstein and Philp, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence from both ends of each insert showed that they encoded full-length copies of klp1 ϩ and klp2 ϩ , respectively. klp1 ϩ was identical to pkl1 ϩ , which has already been described (Pidoux et al, 1996), so this name will be used henceforth. pkl1 ϩ and klp2 ϩ were mapped to the left arm of chromosome I by probing a filter containing ordered arrays of cosmids (Hoheisel et al, 1993), with the use of the original PCR products and with the kind assistance of Dr. Elmar Maier (Imperial Cancer Research Fund, Genome Analysis Laboratory, London).…”
Section: Pcr Strategy For Identifying Klps From the Kar3 Subfamilymentioning
confidence: 99%
“…A complete disruption of the pkl1 ϩ gene has been made with the use of the genomic klp1 ϩ clone described above (Pidoux et al, 1996). A complete replacement of the klp2 ϩ by ura4 ϩ was made by a singlestep gene replacement protocol (Rothstein, 1991), with the use of a cassette containing two genomic regions flanking the either side of the klp2 ϩ gene and ura4 ϩ as the selectable marker.…”
Section: Disruption Of Klp2 ؉mentioning
confidence: 99%
See 1 more Smart Citation